Dawn chorusing in guereza colobus monkeys - Schel, Anne Marijke; Zuberbühler, Klaus (My University, 2012)
Dawn chorusing by guereza black-and-white colobus monkeys is one of the most impressive spectacles of African rainforests. This vocal behaviour is highly contagious, travelling from one neighbouring group to the next, until a wide forest area is covered by calling monkeys. Chorusing usually occurs up to 2 h before dawn, sometimes more than once, unless the preceding night was cold and wet. We conducted a series of playback experiments, which showed that guerezas' chorusing was difficult to elicit experimentally, suggesting that callers took several variables into account before responding to other monkeys' predawn calls. Acoustic analyses showed that morning calls were individually distinct, but we found no evidence that callers took individual identity into account in their decision to participate in chorusing. The only way to reliably elicit chorusing in our study area was to broadcast recordings of morning choruses for longer than 30 s and at a time when a chorus simultaneously emerged in a distant part of the forest.